Melatonin improved glucose homeostasis is associated with the reprogrammed gut microbiota and reduced fecal levels of short‐chain fatty acids in db/db mice. Issue 4 (31st January 2023) - Ban, Qiuyan; Chi, Wenjing; Tan, Yu; Wang, Shiqiong; Li, Ning; Song, Lianjun; Huang, Xianqing; Wang, Dongxu; Peng, Wanxi; Granato, Daniel; Zhao, Guangshan
Abstract: Accumulated evidence shows that melatonin possesses the potential to improve lipid metabolism by modifying gut microbiota and glucose metabolism via regulating the melatonin receptor signaling pathway. However, the contribution of melatonin consumption on glucose homeostasis by affecting gut microbiota has not been investigated in diabetes. In the current work, we investigated the effect of melatonin administration on gut microbiota and glucose homeostasis in db/db mice, a type 2 diabetes model with leptin receptor deficiency. Administration of melatonin through drinking water (at 0.25% and 0.50%) for 12 weeks decreased diabetic polydipsia and polyuria, increased insulin sensitivity and impeded glycemia. The accumulated fecal levels of total short‐chain fatty acids (SCFAs) and acetic acid are positively correlated with diabetes‐related parameters—homeostasis model assessment of insulin resistance (HOMA‐IR) index and fasting blood glucose (FBG) level. The reprogramming of gut microbiota structure and abundance and the reduction of fecal levels of SCFAs, including acetic acid, butyric acid, isovaleric acid, caproic acid, and isobutyric acid, by melatonin may be beneficial for enhancing insulin sensitivity and lowering FBG, which were verified by the results of correlation analysis between acetic acid or total SCFAs and HOMA‐IR and FBG. In addition, the melatonin downregulated hepatic genes, including fructose‐1, 6‐bisphosphatase 1, forkhead box O1 alpha, thioredoxin‐interacting protein, phosphoenolpyruvate carboxy‐kinase (PEPCK), PEPCK1 and a glucose‐6‐phosphatase catalytic subunit, that responsible for gluconeogenesis support the result that melatonin improved glucose metabolism. Overall, results showed that the melatonin supplementation reduced fecal SCFAs level via reprogramming of gut microbiota, and the reduction of fecal SCFAs level is associated with improved glucose homeostasis in db/db mice. Abstract : Our results show that melatonin enhanced insulin sensitivity and impeded glycemia are associated with reduced fecal SCFAs level via reprogramming of gut microbiota structure and abundance. All these data indicate an important association among modified gut microbiota abundance, decreased acetic acid and total SCFAs levels and improved glucose homeostasis. Moreover, melatonin downregulated hepatic genes that responsible for gluconeogenesis support the result that melatonin alleviated glucose dysmetabolism.